2017
DOI: 10.3892/mmr.2017.6488
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing effect of an Astragalus membranaceus polysaccharide and its mechanism

Abstract: In the present study, a novel polysaccharide, APS2-1, was isolated and purified from Astragalus membranaceus using DEAE-cellulose and Sephadex G-100 chromatography. The effect of APS2-1 on the promotion of wound healing was evaluated and its preliminary mechanism was investigated. In vitro experiments showed that APS2-1 was able to promote human skin fibroblast (HSF) propagation and accelerate cell cycle progression. For further examination, a scalded mice model was used to verify the effect of APS2-1 and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 25 publications
7
27
0
1
Order By: Relevance
“…Therefore, the sarcocolla efficacy is more related to the treatment time than with treatment dosage, because we did not find any significant difference in wound-healing ratio between 5% sarcocolla -7 day and 10% sarcocolla-7 day groups and between 5% sarcocolla-14 day and 10% sarcocolla-14 day groups (P > 0.05). Our result is in line with previous studies indicating the protective effects of sarcocolla and other species of Astragalus genus on wound repairing in none diabetic subjects (14,29).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, the sarcocolla efficacy is more related to the treatment time than with treatment dosage, because we did not find any significant difference in wound-healing ratio between 5% sarcocolla -7 day and 10% sarcocolla-7 day groups and between 5% sarcocolla-14 day and 10% sarcocolla-14 day groups (P > 0.05). Our result is in line with previous studies indicating the protective effects of sarcocolla and other species of Astragalus genus on wound repairing in none diabetic subjects (14,29).…”
Section: Discussionsupporting
confidence: 94%
“…Evidence showed that the Astragalus species via different mechanisms including suppressing inflammation, cell cycle acceleration and improving the secretion of repair factors exerts protective effects on wound healing process (29) and future studies are needed to elucidate the exact mechanism of action of A. fasciculifolius on diabetic wound healing. Moreover, other experimental and clinical studies are recommended in order to analyze the possible adverse effects, toxicity or allergic reactions after topical/ systemic use of A. fasciculifolius.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al determined the wound healing effect of an Astragalus membranaceus polysaccharide treatment and its mechanism through in vitro and in vivo studies. The results showed that this polysaccharide was able to promote human skin fibroblast propagation and accelerate cell cycle progression, as well as the reepithelialization, revascularization, and cytokine secretion of TGF-β1, bFGF, and EGF which significantly confirmed the accelerated wound closure in mouse wound model [74]. TGF-β1 is an important promoter in the fibroblast proliferation and the secretion of ECM and inhibits its degradation, while EGF and bFGF are important stimulators in the formation of reepithelialization and keratinocyte migration in wound healing [75].…”
Section: The Effect Of Natural Polysaccharide Structure In Wound Healmentioning
confidence: 70%
“…The importance of glycosylation to wound repair is highlighted by previous studies reporting glycan-mediated increases in epithelial proliferation and wound repair. Specifically, plant root polysaccharides have been shown to promote proliferation, migration, and cell cycle progression in murine and human models of skin wounding (35). Similarly, β-glucan polysaccharides promote migration of dermal fibroblasts, resulting in improved healing of murine skin wounds (36).…”
Section: Discussionmentioning
confidence: 99%